Improved Synthesis of Dbibb as a New Anti-Radiation Agent - Yang, Hong-Peng; Zhang, Shou-Guo; Wang, Gang; Wen, Xiao-Xue; Sun, Yun-Bo; Liu, Shu-Chen; Peng, Tao; Wang, Lin (Chemistry of natural compounds, 2018)
An excellent candidate in the fight against damage caused by nuclear radiation is 2-[4-(1,3-dioxo-1H,3Hbenzoisoquinolin-2-yl)butylsulfamoyl]benzoic acid (DBIBB), a lipid agonist of lysophospholipid acid receptor 2. In this study, a novel method that synthesizes DBIBB was developed. In this method, saccharin was replaced singly by 1,4-dibromobutane, reacted with 1,8-naphthalimide, hydrolyzed by sodium hydroxide, and finally acidified by hydrochloric acid to obtain DBIBB. The new synthesis route was shorter, milder, and simpler than previously reported approaches. The method also produced higher total yield than that of existing ones. Thus, it is applicable to the large-scale synthesis of DBIBB.